Bumbu Rahasia Warteg Bahari: Inovasi Harga Lewat Target Costing dan Activity-Based Costing: Warteg Bahari’s Secret Recipe: Price Innovation Through Target Costing and Activity-Based Costing - Mahefal Absi; Ilham Isnain; Apdas Apdas; Aulia Rahmah; Tri Lestari (CV Warnak Johanna Nusantara, 2025)
large due to rising raw material prices—such as soybeans, which will soar by 30% in 2024—and increasingly fierce market competition. To maintain its competitiveness and business sustainability, Warteg Bahari adopted an innovative strategy through the integration of two modern cost management methods: Target Costing and Activity-Based Costing (ABC). This study aims to explore in depth how these two methods are applied as a “secret sauce” in concocting a competitive selling price (IDR 12,000/portion) while maintaining a profit margin of 25% amid cost fluctuations. Through a qualitative case study approach, data were collected from in-depth interviews with the owner, daily operational observations, and financial document analysis. The results showed that Target Costing was used to determine the maximum production cost limit (IDR 9,000/portion) based on market prices and profit targets. This strategy was implemented through raw material substitution (e.g., chicken replaces more expensive beef, saving up to 15%) and price negotiations with suppliers (saving an average of IDR 2,000/kg). Meanwhile, the application of ABC allows the identification of activities that absorb high costs but are less efficient, such as waste of cooking oil (10% of cooking costs) and suboptimal distribution of working hours. The integration of these two methods can reduce total production costs by up to 18% without reducing product quality. by digital technology, is a